PENGARUH PEMBERIAN JUS BELIMBING (Averrhoa Carambola) DAN BUAH NAGA (Hylocereus Undatus) TERHADAP TEKANAN DARAH PADA PASIEN HIPERTENSI DI RUANG INTERNE RSUD PADANG PANJANG TAHUN 2017 - Nurhamidah, Nurhamidah; Malfita, Mira (IAIN Batusangkar, 2017)
Hypertension is a condition in which a person experiences an increase in blood pressure above normal resulting in increased morbidity and mortality / mortality. Star fruit and dragon fruit can also be used to overcome hypertension. Fruit starfruit and dragon fruit has a lot of antioxidant substances such as vitamin C, Flavonoid and niacin and magnesium that can flex or relax the arterial blood vessels. In addition, star fruit and dragon fruit also have diuretic calcium contents atua peluruh urine so increase the intake of minerals that play a role in lowering high blood pressure. The purpose of this research is to know the effect of juice of star fruit (Averrhoa Carambola) and dragon fruit (hylocereus undatus) to blood pressure in hypertension patient in Internal Room of RSUD Padang Panjang Year 2017.The study was conducted for 6 days with 1 day feeding. The research design used Quasi-Ekperiment using One group pre-post test design on 15 respondents with hypertension. The statistical test obtained p value of systolic blood pressure = 0.000 and p value of diastolic blood pressure = 0.001 then ha accepted, meaning there is influence of star fruit juice and dragon fruit to blood pressure patient room internal hospital RSUD Padang Panjang.Based on the results of this study, researchers suggested that starfruit and dragon juice can be used as an independent intervention, especially for people with hypertension.